A qualitative study on the concept of business planning in the context of leaders of small-medium enterprises - Jamshed, Sanjarih (2021)
All great and successful business leaders and entrepreneurs reiterate that to be successful in leading a business, one has to completely understand the concept of business planning first. A proper business plan not only highlights the business’s core strategies and their execution methodologies but it also serves as a roadmap for the company’s goals and achievements. While, it is possible for an organization to be successful without an in-depth, formatted business plan, but for most entities out there, especially in the modern times where the number of variables in business has increased, it is becoming more and more vital to have a plan that serves as the guiding light for the company’s operations.